OC-090 To determine the negative predictive value of faecal calprotectin in predicting future organic gastrointestinal disease. (23rd September 2015) - Moore, J K; West, S; Kelly, S; Robins, G
Abstract : Introduction: Faecal calprotectin (FC) levels can be used to predict the likelihood of relapse in patients with inflammatory bowel disease (IBD)1 and as a non-invasive marker to predict organic gastrointestinal disease (OGID)2 However, long-term follow-up of patients with low FC levels has not been done. Our aim was to determine whether patients with low FC levels develop OGID over a 5-year period. Methods: York Hospital serves a population of approximately 280 000 and has measured FC where clinically indicated in patients since 2004. Records of patients with a normal FC (<50 μg/g) in 2004 were examined retrospectively. Those with known OGID at the time of index FC measurement were excluded. Primary outcome was diagnosis of an OGID (eg, colorectal cancer or polyps >1 cm, IBD) in the 5 years subsequent to the index FC measurement. The assay used was the PhiCal Calprotectin Elisa kit with a clinical sensitivity of 74% and specificity of 84% at 50 μg/g.3 Results: 118 patients (39 male and 79 female) were identified. The mean age was 40.4 years (SEM 1.3); median age was 41 years (range 15–83). The mean FC level was 13.95 μg/g (SEM 1.04). The median was 10 μg/g (range 5–48). 84 patients were diagnosed with Functional Bowel Disease. No patients during the 5-year follow-up period developed OGID. Conclusion: A normal FC has an extremely high negative predictive value for developing OGID over the subsequent 5 years.